Pensose leggerezze - Dei, Luigi (Dialoghi con la società, 2021)
In this peculiar volume, Luigi Dei gathers a collection of his writings, calling them 'thoughtful lightness' as a tribute to a writer he loves: Italo Calvino. The reference at the beginning of the collection is intended as a sign of appreciation and gratitude towards this great Italian intellectual of the last century. Even the structure of the various sections honors the memory of the writer, recalling his 'Six Memos for the next Millennium'. Brief little stories, animated by the desire to discover everyday life; extracts of speeches characterized by a will to fantasize, imagine and recover the values of visibility; selected parts from greeting speeches on various issues addressed in conferences he attended as a Rector; new theatrical 'stories': all of these are the texts that Luigi Dei manages - with sensitivity and great communication skills - to fill with fantasy, imagination, accuracy, diversity, swiftness and thoughtful lightness. And he's able to do it using a very peculiar language and a captivating style that encourages the reflection on the most important issues of our time.